THE MINI SEINER FLEET OF THE NORTH JAVA COAST: A Case Study of Their Fishing Activities - Jean Marc Ecoutin; Dharmadi Dharmadi (Research Center for Fisheries, 1999)
Fishing effort is often a difficult parameter to identify in halieutic st,udies and even more so if the study involves coastal and artisanal frshing spread along a coast more than 1,000 km long.